Two approaches to reversing language shift and the Soviet publication program for indigenous minorities - Vakhtin, Nikolai (Études/Inuit/Studies, 2005)
AbstractThe present paper discusses the interplay between the Soviet state policy towards indigenous languages of "Northern Minorities" and the attitudes of the indigenous communities to their languages and to language endangerment. The author uses statistics on the Soviet state program of publishing books (primarily school books) in indigenous languages that was launched in the late 1920s and underwent considerable changes in the course of the decades to follow. It is argued that the publishing policy for all languages of indigenous minorities of the Far North followed the same consistent pattern that included several phases: "a glorious beginning" in the 1930s interrupted by the war, then a strong continuation in the 1950s, then a drop in the 1960-70s, and a resurrection in the 1980s, interrupted by the economic crisis of the early 1990s. The most interesting and the least clear period is the two and a half decades between mid-1950s and late 1970s where changes of the state policy may be connected with changes in community attitudes towards their native languages. A successful policy of language preservation and revitalization is possible only if it is supported simultaneously by the state and the indigenous community.